2017
DOI: 10.1371/journal.pone.0188718
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of IgA vasculitis nephritis in children

Abstract: Henoch–Schönlein purpura is a systemic vasculitis characterized by IgA deposits, which target the skin, joints, and kidneys, among other organs. In children, prognosis is often good but little is known about biomarkers of pediatric nephritis. We hypothesized that biological markers, including cytokines, immunoglobulins, IgA-immune complexes, IgA glycosylation and neutrophil gelatinase-associated lipocalin (NGAL), may discriminate IgA vasculitis (IgAV) pediatric patients with renal involvement from those withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
71
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 36 publications
11
71
2
3
Order By: Relevance
“…In one study in children with IgAV with and without nephritis no significant difference in the median serum GD-IgA1 levels was seen at the onset of IgAV [18], while Berthelot et al found i) higher serum levels of GD-IgA1 in 60 adult patients with IgAVN when compared with 25 patients with skin-limited IgAV (they did not explicitly use this term and definition), and ii) slightly, but not significantly increased serum levels in skin-limited IgAV compared to healthy subjects (as in our study) [12]. Similarly, two other studies reported that IgA1 from 24 and 33 children with renal involvement showed significantly higher lectin binding (indicating high GD-IgA1 levels) than IgA1 from 22 and 17 children lacking renal involvement [16,17], while lectin binding of IgA1 from children with IgAV without renal involvement did not differ from healthy subjects [16].…”
Section: Accepted Manuscriptsupporting
confidence: 58%
See 1 more Smart Citation
“…In one study in children with IgAV with and without nephritis no significant difference in the median serum GD-IgA1 levels was seen at the onset of IgAV [18], while Berthelot et al found i) higher serum levels of GD-IgA1 in 60 adult patients with IgAVN when compared with 25 patients with skin-limited IgAV (they did not explicitly use this term and definition), and ii) slightly, but not significantly increased serum levels in skin-limited IgAV compared to healthy subjects (as in our study) [12]. Similarly, two other studies reported that IgA1 from 24 and 33 children with renal involvement showed significantly higher lectin binding (indicating high GD-IgA1 levels) than IgA1 from 22 and 17 children lacking renal involvement [16,17], while lectin binding of IgA1 from children with IgAV without renal involvement did not differ from healthy subjects [16].…”
Section: Accepted Manuscriptsupporting
confidence: 58%
“…We report serum GD-IgA1 levels in precisely phenotyped IgAV patients with systemic and skin-limited IgAV using a specific monoclonal antibody (KM55) based ELISA. Previous studies in adult and pediatric IgAV that have reported serum GD-IgA1 levels have used a lectin-based assay which is known to vary between laboratories [12,16,17]. In one study in children with IgAV with and without nephritis no significant difference in the median serum GD-IgA1 levels was seen at the onset of IgAV [18], while Berthelot et al found i) higher serum levels of GD-IgA1 in 60 adult patients with IgAVN when compared with 25 patients with skin-limited IgAV (they did not explicitly use this term and definition), and ii) slightly, but not significantly increased serum levels in skin-limited IgAV compared to healthy subjects (as in our study) [12].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Various authors have reported higher serum IgA levels in IgA vasculitis patients than in control patients [11]. In our review it was difficult to make a comparison with these results, since most of our patients had no immunoglobulin analytical data, and in the 6 patients with the data only 2 showed elevated levels.…”
Section: Discussionmentioning
confidence: 73%
“…Various predictors of disease recurrence and severity, including GIT and kidney involvement, age, gender, and extent of purpura, have been identified in IgAV, but they cannot be regularly applied to an individual patient . In recent years, the search for biological markers has revealed that the abnormal levels of cytokines and immunoglobulins, the presence of immune complexes and aberrant IgA glycosylation in serum and urine of patients could aid in the diagnosis, monitoring and identification of patients with the severe form of IgAV …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] In recent years, the search for biological markers has revealed that the abnormal levels of cytokines and immunoglobulins, the presence of immune complexes and aberrant IgA glycosylation in serum and urine of patients could aid in the diagnosis, monitoring and identification of patients with the severe form of IgAV. 8,9 Tissue infiltration by neutrophils is a major feature of IgAV. The higher percentage of neutrophils found in the peripheral blood of IgAV patients 9 might thus be related to the presence of neutrophils in skin and other affected organs.…”
Section: Introductionmentioning
confidence: 99%